Efektifitas Model Pembelajaran Otentik (Autentic Learning) dalam Peningkatan Mutu Pembelajaran Pendidikan Agama Islam di SMK Muhammadiyah Kawali Kabupaten Ciamis - Istianah, Aan; Husni, Husni (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2017)
This experimental research succeeds to prove the following conclusion: (1) the application of authentic learning model in PAI learning at SMK Muhammadiyah Kawali Ciamis Regency is done based on authentic experience, and natural. The application of an authentic learning model to the PAI subject is done by the following steps: (a) The teacher opens the learning process by greeting and praying, (b) The teacher administers the class (checks readiness, attendance, seating and other equipment) c) Teachers invite students to tadarus between 5-10 minutes (read/memorize the Qur'an or short selected sura), (d) Teachers provide explanations about the learning objectives to be achieved, (e) Teachers do how far learners understand past learning relationships and/or concepts they have with the materials to be taught); (f) Teachers ask students to do outside classroom learning for three months alternately (between classroom and out of class) in order to gain authentic experience or natural from people who have different religious views. (2) The statistical test using t-test shows that there are differences in the quality of learning in PAI subjects between before and after the implementation of the authentic learning model in significantly different. (3) The subsequent t-test results show significant and significant differences between the groups of students using the authentic learning model (experimental class) with the group of students using the ordinary learning model (control group)